Bridge study protocol: an international, observational cohort study on the transition of healthcare for adolescents with chronic conditions - Kosola Silja; Culnane Evelyn; Loftus Hayley; Tornivuori Anna; Kallio Mira; Telfer Michelle; Miettinen Päivi J; Kolho Kaija-Leena; Aalto Kristiina; Raivio Taneli; Sawyer Susan (BMJ Publishing Group, 2025)
Introduction
More than 10% of adolescents live with a chronic disease or disability that requires regular medical follow-up as they mature into adulthood. During the first 2 years after adolescents with chronic conditions are transferred to adult hospitals, non-adherence rates approach 70% and emergency visits and hospitalisation rates significantly increase. The purpose of the Bridge study is to prospectively examine associations of transition readiness and care experiences with transition success: young patients’ health, health-related quality of life (HRQoL) and adherence to medical appointments as well as costs of care. In addition, we will track patients’ growing independence and educational and employment pathways during the transition process.
Methods and analysis
Bridge is an international, prospective, observational cohort study. Study participants are adolescents with a chronic health condition or disability and their parents/guardians who attended the New Children’s Hospital in Helsinki, Finland, or the Royal Children’s Hospital (RCH) in Melbourne, Australia. Baseline assessment took place approximately 6 months prior to the transfer of care and follow-up data will be collected 1 year and 2 years after the transfer of care. Data will be collected from patients’ hospital records and from questionnaires completed by the patient and their parent/guardian at each time point. The primary outcomes of this study are adherence to medical appointments, clinical health status and HRQoL and costs of care. Secondary outcome measures are educational and employment outcomes.
Ethics and dissemination
The Ethics Committee for Women’s and Children’s Health and Psychiatry at the Helsinki University Hospital (HUS/1547/2017) and the RCH Human Research Ethics Committee (38035) have approved the Bridge study protocol. Results will be published in international peer-reviewed journals and summaries will be provided to the funders of the study as well as patients and their parents/guardians.